Performance improvement in 100KW Photovoltaic grid connected system with Firefly intelligent method under Constant, different irradiation and temperature conditions - et al., Sudheer P (International Journal of Advanced Science and Technology, 2019)
Solar PV cells have remained an active area of research over the past decade and more, with diminishing supplies of fossil fuels and the increasing necessity of renewable energy resources have attracted new path to be explored in the domain of Photo Voltaic cells. Considering the high initial capital cost of a Solar Photovoltaic (SPV) source and its low energy conversion efficiency, it is essential to operate the SPV source at Maximum Power Point (MPP) to extract maximum power under varying solar irradiance and temperatures. In view of the above an attempt has been made in the present work to develop proper algorithm for extraction of maximum power from the solar photovoltaic system (SPV). The scope of the paper includes tracking of Maximum power within less time and oscillations for this a meta-heuristic algorithm Firefly with ANN is utilized to track the maximum power in 100KW Grid connected PV System due to its good features and performance, the firefly algorithm is trained by the ANN technique to get the better power, less power fluctuations, no steady state oscillations, high tracking speed and better working in the change in environmental conditions. Moreover it is compared and showed as better one when compared to the other MPPT algorithms like P&O, PSO, PSO with P&O, P&O, PSO with ABC, Firefly which is implemented in this work.